2015
DOI: 10.1515/popore-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Crinoids from Svalbard in the aftermath of the end−Permian mass extinction

Abstract: Abstract:The end−Permian mass extinction constituted a major event in the history of cri− noids. It led to the demise of the major Paleozoic crinoid groups including cladids, disparids, flexibles and camerates. It is widely accepted that a single lineage, derived from a late Paleo− zoic cladid ancestor (Ampelocrinidae), survived this mass extinction. Holocrinid crinoids (Holocrinus, Holocrinida) along with recently described genus Baudicrinus (Encrinida), the only crinoid groups known from the Early Triassic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The recovery of lower tier, skeletonised biotas was therefore evidently delayed in comparison to soft-bottom communities313262, a phenomenon that we show manifested simultaneously within both low, and mid-high palaeolatitude assemblages. Certainly, some filter feeding organisms such as crinoids seem to have re-diversified earlier in the Boreal Realm (at least after the latest Induan A. fassaensis bivalve zone equivalent63), yet typical encrusters including cyclostome bryozoans and serpulid polychaetes did not fully re-establish until the Rhaetian64. This conspicuous underrepresentation – which is likely not taphonomic because Palaeozoic encrusters possessed similar calcitic skeletons65 and cemented to the substrate throughout the sessile phase of their life cycle – accords with extreme fluctuations in oceanic salinity66, de-oxygenation94067, intense weathering and run-off that are thought to have promoted widespread eutrophication and the proliferation of stromatolite-forming microbial substrates10112668 in the absence of mat-grazing organisms5569.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of lower tier, skeletonised biotas was therefore evidently delayed in comparison to soft-bottom communities313262, a phenomenon that we show manifested simultaneously within both low, and mid-high palaeolatitude assemblages. Certainly, some filter feeding organisms such as crinoids seem to have re-diversified earlier in the Boreal Realm (at least after the latest Induan A. fassaensis bivalve zone equivalent63), yet typical encrusters including cyclostome bryozoans and serpulid polychaetes did not fully re-establish until the Rhaetian64. This conspicuous underrepresentation – which is likely not taphonomic because Palaeozoic encrusters possessed similar calcitic skeletons65 and cemented to the substrate throughout the sessile phase of their life cycle – accords with extreme fluctuations in oceanic salinity66, de-oxygenation94067, intense weathering and run-off that are thought to have promoted widespread eutrophication and the proliferation of stromatolite-forming microbial substrates10112668 in the absence of mat-grazing organisms5569.…”
Section: Discussionmentioning
confidence: 99%
“…in Svalbard (Salamon et al . ) and was assigned to Holocrinidae, Encrinidae, Ainigmacrinidae and Roveacrinida predating the origin of the latter three clades to the Early Triassic. It was concluded that crinoid diversification began earlier in boreal realms than in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…In the boreal realm, a silicified community of late Griesbachian and Dienerian crinoid sclerites has been recovered from the Vardebukta Fm. in Svalbard (Salamon et al 2015) and was assigned to Holocrinidae, Encrinidae, Ainigmacrinidae and Roveacrinida predating the origin of the latter three clades to the Early Triassic. It was concluded that crinoid diversification began earlier in boreal realms than in the tropics.…”
Section: On the Origin Of Holocrinidsmentioning
confidence: 99%
“…) and Festningen, Svalbard (Salamon et al . ). The occurrence of Holocrinus on the Great Bank of Guizhou and in western Zhejiang (Chen et al .…”
Section: Cf Holocrinus Sp Figure Nmentioning
confidence: 97%